Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Apoidea (Spheciformes), Heterogynaidae - Gadallah, Neveen S. (Zootaxa, 2020)
An updated checklist of the Arabian species of Heterogynaidae is provided here. The list includes two identified valid species in one genus. Distributions on the Peninsula are provided for each species; both (100%) are endemic to the Arabian Peninsula.